(untitled) (American Journal of Islam and Society, 1994)
The eclipse of Arabic that took place in the last part of the eighteenth and the early nineteenth century was caused by several factots. This paper looks at the mxons for this eclipse and also sheds light on the revival of Arabic in the Arab world in general and in Syria in particular. The conquest of Syria and Egypt by Salim I in 1516 and 1517 marks a definite stage in the extension of Ottoman sway over the Arab world. His crushing victories made him the master of Iraq and Syria and enabled him to enter Cairo and establish his rule over Egypt. Under his successor, Sulaymh the Magnificent, the subjection of the Arab world was extended westward along the North African coast and southward as far as Yemen and Aden. Upon Stdaymiin’s death in 1566, the Ottomans ruled the Arab world from Algeria to the Arabian Gulf, and from Aleppo to the Indian Ocean. In addition to the sacred cities of Makkah, Madinah, and Jerusalem, it embraced Damascus, the fitst capital of the Arab empire, and Baghdad, whose sciences had once illuminated the world. With varying fortunes, and frequently accompanied by war and revolt, the Ottoman Empire maintained itself in these territories until the end of the eighteenth century and the outbreak of the First World War in 1914. At the beginning of the eighteenth century, the Ottoman Empire witnessed a movement of reform and reorganization under Abmad III(1703- 30) and his successors. However, the Arab world did not seem to benefit very much from it. In addition, these reforms, intended primarily to arrest the Empire’s decline and restore vitality to its system, sought to establish Turldsh as the language of instruction. Later on, Arabic was abandoned and Turkish became the language of instruction in government schools and educational institutions.‘ Only Arabic grammatical rules, which were indispensable for an understanding of Ottoman literature, were taught and, quite often, by Turkish teachers ...